Critical Discourse Analysis of Distance Higher Education in Turkish Higher Education Policy Documents - Altunoğlu, Asu (Journal of Applied And Theoretical Social Sciences, 2024)
This study examines the distance higher education related policy strategies of the Turkish state. Using critical discourse analysis, based on Norman Fairclough’s work, the aim is to analyse the discourses used within policy-related documents and government reports regarding the role and significance of distance education in the Turkish higher education system. In order to achieve this objective, certain key documents including annual activity reports, national youth and education policy documents, and strategic plans produced by the Ministry of National Education and Higher Education Council have been analyzed. Basic findings reveal that in the dominant discourses regarding distance education in the Turkish higher education system, the policy makers seem to have very little interest in distance education as a strategic tool. The superficiality and indifference towards the open university system in the analysed documents may come to mean that the policies and envisaged programmes are far away from any solid theoretical background in how distance education may contribute to social inclusion and the development of the society through higher education of masses. Thus, this study can conclude that achieving social justice in distance education in Türkiye requires a devoted undestanding of its contributions to inclusion of all kinds of lifelong learners with diverse needs.